Mediation as One of the Communication Modes in Theory and Practice - Hradilová, Darina (Bohemistyka, 2025)
The paper explores mediation as one of the modes of communication. In general, it demonstrates how mediation is perceived in relevant scholarly sources, such as the Common European Framework of Reference for Languages, and to what extent theoretical descriptors correspond to the actual communication needs of everyday life. Furthermore, the article examines whether and how selected teaching materials support the development of mediation skills. The paper presents the results of research that investigated how speakers acquiring Czech as a foreign language perceive their needs within this communicative mode, their experience with mediation, and their competences in this mode of communication. The outcomes of the conducted research indicate that students possess only average mediation skills and consider only certain specific mediation activities to be purposeful. These activities should therefore be the focus of instruction, enabling students to consciously and competently apply mediation as a communicative mode.